The Influence of Principal Leadership and Work Motivation on Teacher Performance at Elementary Schools in Poigar District - Sagita Healthy Mongkol; Hetty Julita Tumurang; Marssel Michael Sengkey (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The influence of principal leadership and teacher work motivation in elementary schools in Poigar district. This research aims toTo determine the influence of principal leadership and work motivation on teacher performance in Poigar District Elementary School. This study uses a quantitative approach with an associative research type. The research subjects were 220 teachers in Poigar District. Data collection techniques were through observation, questionnaires using a Likert scale and documentation. The research instrument in the form of a questionnaire measured data on principal leadership, work motivation, and teacher performance. The data were analyzed using descriptive statistical analysis, analysis prerequisite tests in the form of normality, linearity, multicollinearity, heteroscedasticity tests and continued with multiple regression analysis, t-test, f-test, and determination coefficient r. The results of the study showed 1) there was a significant influence of principal leadership on teacher performance with a sig. 0.01 <0.05 and 7.149 > 1.971, so it was concluded that it was accepted. 2) there was an influence of teacher work motivation on teacher performance with a sig. 0.03 <0.05 and 7.013 > 1.971, so it was concluded that it was accepted. 3) There is an influence of principal leadership and teacher work motivation on teacher performance with a sig. 004 < 0.05 and a value of 29.934 > 3.04, then accepted, with the results of the coefficient of determination showing that principal leadership and work motivation contribute 60.8%. Thus, it can be concluded that principal leadership and work motivation have a significant influence on teacher performance at Poigar District Elementary School.t_hitung t_tabel H_1 t_hitung t_tabel H_2 F_hitung F_tabel H_3 Keywords :Principal leadership, work motivation and teacher performance.